Law Enforcement of Money Politics Criminal Offenses in the 2024 General Election for the Regional House of Representatives (Study at the General Election Supervisory Agency of Surabaya City) - Ardan, Muhammad; Maeyangsari, Dessy (fakultas hukum universitas PGRI Semarang, 2025)
Abstract: The general election is a constitutional mechanism conducted every five years to elect representatives, including members of the Regional House of Representatives, according to the 1945 Constitution of the Republic of Indonesia and Law Number 7 of 2017. One of the main challenges in its implementation is the practice of money politics, which constitutes a general election criminal offense. This study discusses money politics’ classification and law enforcement in the 2024 Regional House of Representatives general election in Surabaya City. The method used is empirical legal research combined with law enforcement theory. Money politics occurred during the campaign period, the quiet period, and on election day, with five reports submitted to the General Election Supervisory Agency of Surabaya City. However, all were dismissed due to failing to meet the elements of legal subject, act, and intent. Obstacles to law enforcement include legal factors, law enforcement officers, facilities and infrastructure, society, and culture. The primary recommendations are education, strengthened supervision, and improvements in the recruitment system. Keywords: Law Enforcement, Money Politics, General Election, the Regional House of Representatives, the General Election Supervisory Agency Of Surabaya City.